Students with special educational needs in distance learning during the COVID-19 pandemic – parents’ opinions - Trzcińska-Król, Maria (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
This article focuses on how children with special educational needs, psychological and pedagogical opinions and advice and guidance on how to work with them, and their parents are coping in a distance learning situation. Four research problems have been formulated, i.e., What changes do parents notice in the child’s motivation to learn during distance learning education? What limitations and difficulties arise with distance learning education? What are the attitudes of children during distance learning in the opinions of their parents? Do parents notice any progress in their children’s learning during distance learning education? For research on the key methods used and interview technique. The research was conducted on the basis of the opinions of parents, who during distance learning education were strongly involved in the educational processes of their children, and often took on the role of a teacher. Self-study for children is limited by the challenge, cannot be met, and remote learning evokes great emotions in them. In the opinion of parents, distance learning education tools are not conducive to the focus of attention on the part of their children.